Associations between dual‐decline in cognition and gait speed with risk of dementia – results from the ASPREE trial cohort. (20th December 2022) - Collyer, Taya; Murray, Anne; Woods, Robyn; Storey, Elsdon; Chong, Trevor; Ryan, Joanne; Orchard, Suzanne; Brodtmann, Amy; Srikanth, Velandai K; Shah, Raj C; Callisaya, Michele L
Abstract: Background: Dual decline in gait speed and cognition is associated with an increased risk of dementia. However, it is unclear if risks are conferred by decline in domain‐specific cognition and gait. We aimed to examine associations between dual decline in gait speed and cognition (global cognition, memory, processing speed and verbal fluency) with risk of dementia. Methods: Prospective cohort study. Participants were from the ASPREE (ASPirin in Reducing Events in the Elderly) study, a double‐blind, randomized, placebo‐controlled trial of low dose aspirin in older adults (≥70 years; ≥65 if US minority). Of 19, 114 randomized participants, 16, 855 (88%) had longitudinal gait and cognitive data. Gait speed was measured at 0, 2, 4, 6 years and close‐out. Cognitive measures included Modified Mini‐Mental State examination (3MS, global cognition), Hopkins Verbal Learning Test‐Revised (HVLT‐R, memory), Symbol Digit Modalities (SDMT, processing speed) and Controlled Oral Word Association Test (COWAT‐F, verbal fluency), assessed at years 0, 1, 3, 5, and close‐out. Participants were classified into four groups: 1) dual decline in gait and cognition; 2) gait decline only; 3) cognitive decline only and 4) non‐decliners. Cognitive decline was defined as membership of the lowest tertile of annual change. Gait decline was defined as decline in gait speed ≥0.05 m/s per year across the study. Dementia (DSM‐IV criteria) was adjudicated by an expert panel using cognitive tests, functional status and clinical records. Cox proportional hazard models were used to estimate risk of dementia adjusting for covariates with death as competing risk. Results: The mean age of participants was 75.0 (SD4.4) years. Compared with non‐decliners, risk of dementia was highest in the gait+HVLT‐R decliners (HR 24.7; 95% CI 16.3‐37.3), followed by the gait+3MS (HR 22.2; 95% CI 15.0‐32.9), gait+COWAT‐F (HR 4.66 95%; CI 3.5‐6.3) and gait+SDMT (HR 4.3 95% CI 3.2‐5.8) groups. Dual decliners also had higher risk of dementia than those with either gait or cognitive decline alone for 3MS and HVLT‐R. Conclusion: The combination of decline in gait speed and memory may be the best suited to predict future dementia risk.